Multiparametric renal magnetic resonance imaging: A reproducibility study in renal allografts with stable function. (10th October 2022) - Echeverria‐Chasco, Rebeca; Martin‐Moreno, Paloma L.; Garcia‐Fernandez, Nuria; Vidorreta, Marta; Aramendia‐Vidaurreta, Verónica; Cano, David; Villanueva, Arantxa; Bastarrika, Gorka; Fernández‐Seara, Maria A.
Abstract : Monitoring renal allograft function after transplantation is key for the early detection of allograft impairment, which in turn can contribute to preventing the loss of the allograft. Multiparametric renal MRI (mpMRI) is a promising noninvasive technique to assess and characterize renal physiopathology; however, few studies have employed mpMRI in renal allografts with stable function (maintained function over a long time period). The purposes of the current study were to evaluate the reproducibility of mpMRI in transplant patients and to characterize normal values of the measured parameters, and to estimate the labeling efficiency of Pseudo‐Continuous Arterial Spin Labeling (PCASL) in the infrarenal aorta using numerical simulations considering experimental measurements of aortic blood flow profiles. The subjects were 20 transplant patients with stable kidney function, maintained over 1 year. The MRI protocol consisted of PCASL, intravoxel incoherent motion, and T1 inversion recovery. Phase contrast was used to measure aortic blood flow. Renal blood flow (RBF), diffusion coefficient (D), pseudo‐diffusion coefficient (D*), flowing fraction ( f ), and T1 maps were calculated and mean values were measured in the cortex and medulla. The labeling efficiency of PCASL was estimated from simulation of Bloch equations. Reproducibility was assessed with the within‐subject coefficient of variation, intraclass correlation coefficient, and Bland‐Altman analysis. Correlations were evaluated using the Pearson correlation coefficient. The significance level was p less than 0.05. Cortical reproducibility was very good for T1, D, and RBF, moderate for f, and low for D*, while medullary reproducibility was good for T1 and D. Significant correlations in the cortex between RBF and f (r = 0.66), RBF and eGFR (r = 0.64), and D* and eGFR (r = −0.57) were found. Normal values of the measured parameters employing the mpMRI protocol in kidney transplant patients with stable function were characterized and the results showed good reproducibility of the techniques. Abstract : Reproducibility of a multiparametric MRI protocol including Pseudo‐Continuous Arterial Spin Labeling (PCASL), intravoxel incoherent motion (IVIM), and T1 mapping sequences was assessed, and normal values of the measured parameters were characterized in renal transplant patients with stable function.